Nanoengineering of Aligning Cibacron Brilliant Yellow Using Light: Application in Flexible Displays - M. M., Yusoff; Hegde, Gurumurthy; V. G., Chigrinov; Hoi, Sing Kwok (2012)
Photoalignment properties on commercially available textile dye cibacron brilliant yellow exhibits extraordinarily high photo-and thermal stability. The distinguished alignment properties of this dye extend the field of the sulfuric azo dyes effective for photoalignment. An attractive feature of this dye is its low curing temperature which is essential for plastic substrates to use it as flexible devices.